Modeling of the catalytic cracking: Catalyst deactivation by coke and heavy metals; Fuel Processing Technology; Vol. 200 - Nazarova G. Yu. Galina Yurievna; Ivashkina E. N. Elena Nikolaevna; Ivanchina E. D. Emilia Dmitrievna; Oreshina A. A. Aleksandra Aleksandrovna; Dolganova I. O. Irena Olegovna; Pasyukova M. A. Mariya Alekseevna (2020, 2020)
Title screen